2016
DOI: 10.15407/ubj88.06.076
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum ferritin levels and serum lipids and HDL function with respect to age and gender

Abstract: Elevated serum ferritin (SFer) levels have been associated with chronic diseases such as coronary heart disease and diabetes mellitus type 2. The aim of this study was to examine the relationship between SFer levels and serum lipid parameters, and how this relation changes in terms of age and gender. Additionally, we investigated a possible relationship between SFer levels and high-density lipoprotein (HDL) function. SFer levels and lipid panel (total cholesterol (TC), triglyceride (TG), low-density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Ferritin levels have been associated with atherogenic lipid profiles in previous studies. It has been reported a negative correlation between levels of serum ferritin and HDL-cholesterol, while positive correlations between levels of serum ferritin and total cholesterol, triglyceride, and LDL-cholesterol 25 . In the present study, for the first time, we demonstrate that ferritin in postmenopausal women participating in RT over 15 weeks was positively correlated with atherogenic lipids including triglycerides, non-HDL and apolipoprotein-B, while negatively correlated with HDL.…”
Section: Discussionmentioning
confidence: 98%
“…Ferritin levels have been associated with atherogenic lipid profiles in previous studies. It has been reported a negative correlation between levels of serum ferritin and HDL-cholesterol, while positive correlations between levels of serum ferritin and total cholesterol, triglyceride, and LDL-cholesterol 25 . In the present study, for the first time, we demonstrate that ferritin in postmenopausal women participating in RT over 15 weeks was positively correlated with atherogenic lipids including triglycerides, non-HDL and apolipoprotein-B, while negatively correlated with HDL.…”
Section: Discussionmentioning
confidence: 98%
“…Apo -apolipoprotein triglycerides, as well as LDL, and a negative correlation between ferritin and HDL 130. …”
mentioning
confidence: 89%
“…[125][126][127][128] Recent studies have reported associations between increased ferritin levels and increases in lipids, including total cholesterol, triglycerides, and LDL, in patients with CVD. 129,130 Thus, in the Strength study, we aimed to analyse if RT could alter the plasma lipid profile and iron status in postmenopausal women.…”
Section: Rt Associated Effects On Iron Status and Lipids (Paper Iv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated SF levels are closely related to chronic diseases such as type 2 diabetes (T2D) and cardiovascular disease. Correlation analyses revealed a nega-tive correlation between the levels of SF and high-density lipoprotein cholesterol (HDL-C), while positive correlations existed between the levels of SF and triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) [3].…”
Section: Introductionmentioning
confidence: 99%